From teacher training to reader/literary training in Youth and Adult Education: theoretical and research perspectives in late modernity - Carvalho, Aldenora Márcia Chaves Pinheiro; Nóbrega, Maria Marta dos Santos Silva (Revista Letras Raras, 2025)
Aiming to establish relationships of approximation and distance between the conceptual instruments worked on by contemporary theorists in the different sectors of knowledge in the human and social sciences, specifically in education; this work aims to situate some theoretical and research approaches to teacher training, regarding the training of student-readers/literature in Youth and Adult Education - EJA. In this sense, based on the ideas of Morin (2008), Canclini (2008), Giddens (2002), Hall (2006), Foucault (2010) and Bourdieu (2004) in the scope of cultural studies, we will discuss issues about teacher professionalization based on from the assumptions of Novoa (2017), also, the knowledge of training in Tardif (2010) and about the teacher's work in Amigues (2004) and Schön (2008). Methodologically, this work is bibliographic in nature, based on a literature review on the themes listed as categories of analysis, namely: teacher training, student-reader training and literary reading in Youth and Adult Education - EJA . Following this line, we aim to discuss these relationships from the perspective of post-colonial cultural studies, analyzing the connections between such conceptions and their reflections on human and social movements.